From matter to spirit: metaphors of enlightenment in Bhagavad-gītā - Kumaran Rajandran, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The article examines the use of metaphors in a prominent Hindu scripture named Bhagavadgītā. Although Hindu scriptures have been analyzed for centuries, the focus is rarely on metaphors. Bhagavad-gītā has 700 verses in 18 chapters and it records a historical conversation between Lord Krishna and Prince Arjuna. Krishna teaches Arjuna philosophical concepts, which are frequently articulated through metaphors. The article selects an English translation of Bhagavad-gītā by Swami Prabhupāda and it pursues a text analysis, which is grounded in conceptual metaphor theory (CMT). The analysis identifies the source and target domains for the metaphors, and interprets their functions. The article only explores metaphors of enlightenment, as Bhagavad-gītā instructs people to become enlightened. The concept of enlightenment is conceptualized by ENLIGHTENMENT IS A JOURNEY, KNOWLEDGE IS SIGHT, KNOWLEDGE IS TASTE and KNOWLEDGE IS AN OBJECT. Bhagavad-gītā conceives people as body, mind and soul because a body and mind (matter) are required to understand a soul (spirit). It endorses four yogas or methods (devotion, meditation, transcendental knowledge, virtuous acts) to obtain the results of enlightenment, which terminate reincarnation and grant Paradise. Bhagavad-gītā lists two guides (mentor, scripture) although personal endeavor must be invested to move from matter to spirit. The article traces the choice of metaphors to physical and cultural experiences, besides the motivation of the translator. These metaphors may be inspired by the human body or ancient India but they should resonate with modern people. Moreover, Prabhupāda’s translation utilizes the metaphors to make Vaishnavism comprehensible to Westerners and to validate the denomination.